Management of Nociceptive Pain for Third-Year Medical Students-Team Based Learning (TBL) Format - Nathalie K. Zgheib; Ghassan Kanazi; Wael Saasouh (Association of American Medical Colleges, 2012)
Abstract This team-based learning (TBL) module covers the use of nonsteroidal anti-inflammatory drugs (NSAIDs), nonopioid, and opioid analgesics in the treatment of nociceptive pain. Students will be required to establish a treatment plan for cases of nociceptive pain and apply multimodal analgesia when appropriate. This TBL case is one of seven bimonthly TBL modules used in the clinical pharmacology course that is offered to third-year medical students at the American University of Beirut Faculty of Medicine. This individual case has so far been used more than six times. We did not evaluate outcomes of each individual module, so the positive outcomes we observed are for the course as a whole. Nevertheless, we have been observing a very high level of student-to-student interaction during all modules in general. Furthermore, as expected with TBL performance on the group readiness assurance test has always been significantly better than performance on the individual readiness assurance test.